Herbivore-specific induction of indirect and direct defensive responses in leaves and roots. Issue 1 (1st February 2019) - Xiao, Li; Carrillo, Juli; Siemann, Evan; Ding, Jianqing
Abstract: Herbivory can induce both general and specific responses in plants that modify direct and indirect defence against subsequent herbivory. The type of induction (local versus systemic induction, single versus multiple defence induction) likely depends both on herbivore identity and relationships among different responses. We examined the effects of two above-ground chewing herbivores (caterpillar, weevil) and one sucking herbivore (aphid) on indirect defence responses in leaves and direct defence responses in both leaves and roots of tallow tree, Triadica sebifera. We also included foliar applications of methyl jasmonate (MeJA) and salicylic acid (SA). We found that chewing herbivores and MeJA increased above-ground defence chemicals but SA only increased below-ground total flavonoids. Herbivory or MeJA increased above-ground indirect defence response (extrafloral nectar) but SA decreased it. Principal component analysis showed there was a trade-off between increasing total root phenolics and tannins (MeJA, chewing) versus latex and total root flavonoids (aphid, SA). For individual flavonoids, there was evidence for systemic induction (quercetin), trade-offs between compounds (quercetin versus kaempferitrin) and trade-offs between above-ground versus below-ground production (isoquercetin). Our results suggest that direct and indirect defence responses in leaves and roots depend on herbivore host range and specificity along with feeding mode. We detected relationships among some defence response types, while others were independent. Including multiple types of insects to examine defence inductions in leaves and roots may better elucidate the complexity and specificity of defence responses of plants. Abstract : Few studies have investigated to what degree herbivory can induce both highly specific and broad chemical changes in plants across different defence classes. This study examined the effects of multiple herbivores and two plant signalling hormones on indirect defence and direct defence responses in leaves and roots of Triadica sebifera . We provide evidence that the different herbivores can induce highly specific plant responses; moreover, the simultaneous and relative induction of different defence types depends on the herbivore identity and plant part (roots versus shoots).